Recent developments and advances of FGFR as a potential target in cancer. (1st August 2018) - Xue, Wen-Jun; Li, Ming-Tao; Chen, Lin; Sun, Li-Ping; Li, Yu-Yan
FGFs and their receptors (FGFRs) are critical for many biologic processes, including angiogenesis, wound healing and tissue regeneration. Aberrations in FGFR signaling are common in cancer, making FGFRs a promising target in antitumor studies. To date, many FGFR inhibitors are being detected in clinical studies, and resistance to some inhibitors has emerged. Understanding the mechanisms of resistance is a fundamental step for further implementation of targeted therapies. In this review, we will describe the basic knowledge regarding FGF/FGFR signaling and categorize the clinical FGFR inhibitors. The mechanisms of resistance to FGFR inhibitors and corresponding strategies of overcoming drug resistance will also be discussed.